Editorial practices and policies of scientific journals that make authors uncomfortable - Ganga-Contreras, Francisco; Alarcón, Nancy; Suárez-Amaya, Wendolin; Álvarez-Maldonado, David (Iberoamerican Journal of Science Measurement and Communication, 2024)
Objective. The editorial practices and policies of scientific journals that were uncomfortable for authors were identified with the objective of eliciting feedback to enhance collaboration between authors and editors. Methodology. The focus group technique was employed. Based on the content of the discussions, a descriptive analysis of the primary concepts was conducted, represented by word mapping and a treemap. Subsequently, the codes obtained were categorized into four dimensions: (1) editorial standards and formats, (2) selection and acceptance process, (3) peer review and evaluation, and (4) role of editors. Results. The most frequently cited issues by the focus group participants were delays in the editorial process and a perceived lack of editorial transparency. Other challenges identified include the following: (1) a lack of clarity in standards, primarily due to the inconsistency in editorial requirements; (2) a lack of adequate feedback; (3) limitation in the number of authors; and (4) constraints in the number of publications. Conclusions. A critical and reflective approach was employed to examine the editorial practices that affect scientific production. The necessity for reforms in the publishing system to enhance the quality, equity, and efficiency of the publication process was emphasized, with the aim of ensuring that scientific progress can significantly benefit global knowledge. Through a concerted and collaborative effort between authors, editors, and reviewers, it will be possible to pursue a trajectory of continuous improvement, wherein the advancement of high-quality scientific research will continue to be facilitated.